IL-6 in the Ecosystem of Head and Neck Cancer: Possible Therapeutic Perspectives - Španko, Michal; Strnadová, Karolína; Pavlíček, Aleš Jan; Szabo, Pavol; Kodet, Ondřej; Valach, Jaroslav; Dvořánková, Barbora; Smetana, Karel; Lacina, Lukáš (International journal of molecular sciences, 2021)
Interleukin-6 (IL-6) is a highly potent cytokine involved in multiple biological processes. It was previously reported to play a distinct role in inflammation, autoimmune and psychiatric disorders, ageing and various types of cancer. Furthermore, it is understood that IL-6 and its signaling pathways are substantial players in orchestrating the cancer microenvironment. Thus, they appear to be potential targets in anti-tumor therapy. The aim of this article is to elucidate the role of IL-6 in the tumor ecosystem and to review the possible therapeutic approaches in head and neck cancer.
Keywords: zánět; nádorové mikroprostředí; signální transdukce; head and neck cancer; Interleukin-6; targeted therapy; cancer microenvironment; nádory hlavy a krku; lidé; Head and Neck Neoplasms; Inflammation; Tumor Microenvironment; IL-6; interleukin-6; Humans; Signal Transduction